The health status of adults on the autism spectrum. (October 2015) - Croen, Lisa A; Zerbo, Ousseny; Qian, Yinge; Massolo, Maria L; Rich, Steve; Sidney, Stephen; Kripke, Clarissa
Compared to the general pediatric population, children with autism have higher rates of co-occurring medical and psychiatric illnesses, yet very little is known about the general health status of adults with autism. The objective of this study was to describe the frequency of psychiatric and medical conditions among a large, diverse, insured population of adults with autism in the United States. Participants were adult members of Kaiser Permanente Northern California enrolled from 2008 to 2012. Autism spectrum disorder cases ( N = 1507) were adults with autism spectrum disorder diagnoses (International Classification of Diseases-9-Clinical Modification codes 299.0, 299.8, 299.9) recorded in medical records on at least two separate occasions. Controls ( N = 15, 070) were adults without any autism spectrum disorder diagnoses sampled at a 10:1 ratio and frequency matched to cases on sex and age. Adults with autism had significantly increased rates of all major psychiatric disorders including depression, anxiety, bipolar disorder, obsessive–compulsive disorder, schizophrenia, and suicide attempts. Nearly all medical conditions were significantly more common in adults with autism, including immune conditions, gastrointestinal and sleep disorders, seizure, obesity, dyslipidemia, hypertension, and diabetes. Rarer conditions, such as stroke and Parkinson's disease, were also significantly more common among adults with autism. Future research is needed to understand the social, healthcare access, and biological factors underlying these observations.